A semi-analytical method for the springback prediction of thick-walled 3D tubes. (5th June 2016) - Zhang, Z.K.; Wu, J.J.; Guo, R.C.; Wang, M.Z.; Li, F.F.; Guo, S.C.; Wang, Y.A.; Liu, W.P.
Abstract: The aim of this paper is to investigate the deformation and springback behavior of 3D tubes under complex stress conditions. We proposed a new semi-analytical method to predict the springback behavior of 3D tubes. In the new method, discretization and approximation are implemented on the tube axis so that the deformation parameters (bending radiuses and twisting angles) can be derived. Based on the discretization and approximation, a theoretical model is proposed to calculate the stress distributions and residual deformations. The new method is applied on a typical 3D tube for springback prediction, and comparison between theoretical and experimental results shows a remarkable agreement. Additionally, it is also found that the radii after springback will decrease inversely with the increase of twisting angle, and this tendency will become clearer when the bending radius increases. Graphical abstract: Highlights: A new method with discretization and approximation implemented on the tube axis to predict the springback of 3D tubes Based on elastic-perfectly plastic material model, formulas for springback prediction are established. For bending and twisting process, radius after springback decreases inversely with the increase of twisting angle.